STUDI EKSEGETIS UNGKAPAN “TUBUHMU ADALAH BAIT ROH KUDUS” BERDASARKAN 1 KORINTUS 6:19 - Manase Gulo (Sekolah Tinggi Teologi Arastamar Bengkulu, 2016)
The concept of doctrine influences the actions of human life. True doctrine and also believed will provide insight into the correct thinking. However, if a doctrine that is not in accordance with the truth and is believed will affect one's life attitude becomes problematic. One of them is the problem of morality. The wrong understanding of the body will lead people to the wrong attitude about life about the body. The lower the assessment of the human eating body the more does not respect the body. But there is a danger when humans are increasingly valuing the body it can become narcissism. 1 Corinthians 6:19 is a verse that is often debated and interpreted to establish morality about the body. Therefore through this writing, we try to open human understanding of the body from a biblical perspective.